Effects of L-methionine on growth performance, carcass quality, feather traits, and small intestinal morphology of Pekin ducks compared with conventional DL-methionine. (27th July 2019) - Zhang, Y N; Xu, R S; Min, L; Ruan, D; Kim, H Y; Hong, Y G; Chen, W; Wang, S; Xia, W G; Luo, X; Xie, C Y; Shang, X G; et al.
Abstract: The research studied the effects of l -methionine (l -Met) on growth performance, carcass quality, feather traits, and small intestinal morphology of Pekin ducks compared with conventional dl -methionine (dl -Met). A total of 1080, 1-day-old male Pekin ducks were randomly allotted to 9 groups with 6 replicate pens of 20 birds each. During the starter phase (1 to 14 d), ducks were fed a basal diet (Met, 0.30%) or that supplemented with dl -Met or l -Met at 0.05, 0.10, 0.15, or 0.20% of feed. During the grower phase (15 to 35 d), ducks were fed a basal diet (Met, 0.24%) or that supplemented with dl - Met or l -Met at 0.04, 0.08, 0.12, or 0.16% of feed. Compared with ducks fed the basal diet, supplementation with either dl - Met or l -Met increased the body weight (BW ) of ducks at days 14 and 35, increased average daily gain (ADG ) and average daily feed intake (ADFI ), decreased F:G at the starter phase, and increased ADG over the whole 35-d period ( P < 0.05). The efficacy of l -Met compared to dl - Met was 140.1% for 14-d BW, 137.6% for ADG and 121.0% for F:G for days 1 to 14. Ducks fed diets supplemented with l -Met had greater proportion of leg muscle, higher than in ducks provided with dl - Met ( P < 0.05). The breast muscle proportion was enhanced with dl - Met rather than l - Met supplementation ( P < 0.01). The back feathers score and fourth primary wing feather length were increased with dl - Met or l -Met supplementation ( P < 0.01), and there was increased efficacy of l -Met relative to dl - Met for back feathers score (153.1%). Dietary dl - Met or l - Met supplementation increased villus height of ileal mucosa of ducks at days 14 and 35 ( P < 0.01). Overall, dietary l -Met or dl - Met supplementation affected the growth performance of ducks during the starter phase, and improved the feather traits and small intestinal morphology. The efficacy of l -Met to dl - Met ranged from 120 to 140% for growth performance of young ducks (1 to 14 d) and was 153% for the feather traits of ducks (35 d).